The effectiveness of a 12-day training program restoring aerobic capacity after a break in training at football players` - Gabrys, T.; Garnys, M.; Stanula, A.; Szmatlan-Gabrys, U.; Szczerbowski, M. (Studia Sportiva, 2017)
The occurrence of detraining in sports disciplines characterized by an extended starting period has to be taken into consideration whilst devising the sports training program. The aim of this study was the evaluation of the effectiveness of the applied 12-day training program, which was to minimalize the effects of detraining in a group of Polish Major League football players. The training program applied, based on a total load volume, in two micro cycles in the particular zones: Io 28, and 31 km, IIo 24, and 26.5 km, IIIo 18, and 19.8 km, influences a significant aerobic capacity precipitation of competitors after a 14-day detraining period. The increase of indicator value were: VO2max by 12%, V.LT by 7%, and V.AT by 10%. Due to choosing the proportions of training loads in I, II, and III intensity range, it is possible to include competitors with various levels of aerobic capacity in one training group. The basis of such a solution is determining individual workout intensities while the volume is the same for the whole team.